Photoconversion Optimization of Pulsed-Laser-Deposited p-CZTS/n-Si-Nanowires Heterojunction-Based Photovoltaic Devices - Zakaria Oulad Elhmaidi; Mohammed Abd-Lefdil; My Ali El Khakani (Nanomaterials, 2020)
We report on the achievement of novel photovoltaic devices based on the pulsed laser deposition (PLD) of p-type Cu2ZnSnS4 (CZTS) layers onto n-type silicon nanowires (SiNWs). To optimize the photoconversion efficiency of these p-CZTS/n-SiNWs heterojunction devices, both the thickness of the CZTS films and the length of the SiNWs were independently varied in the (0.3–1.0 µm) and (1–6 µm) ranges, respectively. The kësterite CZTS films were directly deposited onto the SiNWs/Si substrates by means of a one-step PLD approach at a substrate temperature of 300 °C and without resorting to any post-sulfurization process. The systematic assessment of the PV performance of the ITO/p-CZTS/n-SiNWs/Al solar cells, as a function of both SiNWs’ length and CZTS film thickness, has led to the identification of the optimal device characteristics. Indeed, an unprecedented power conversion efficiency (PCE) as high as ~5.5%, a VOC of 400 mV, a JSC of 26.3 mA/cm2 and a FF of 51.8% were delivered by the devices formed by SiNWs having a length of 2.2 µm along with a CZTS film thickness of 540 nm. This PCE value is higher than the current record efficiency (of 5.2%) reported for pulsed-laser-deposited-CZTS (PLD-CZTS)-based solar cells with the classical SLG/Mo/CZTS/CdS/ZnO/ITO/Ag/MgF2 device architecture. The relative ease of depositing high-quality CZTS films by means of PLD (without resorting to any post deposition treatment) along with the gain from an extended CZTS/Si interface offered by the silicon nanowires make the approach developed here very promising for further integration of CZTS with the mature silicon nanostructuring technologies to develop novel optoelectronic devices.